RETRACTED: The influence of the chlorella suspension on morphometric parameters of different taxonomical groups plants seedlings - Dudina Iuliia; Kalashnikova Elena; Kirakosyan Rima (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001